Meaning in life among nursing students: a latent profile analysis - Zhixin Zhao; Yongxia Mei; Xiaoxuan Wang; Hu Jiang; Wenna Wang; Beilei Lin; Zhenxiang Zhang (BMC, 2023)
Abstract Background Meaning in life, defined by an individual's understanding and appreciation of life, is a vital aspect of a positive psychological state, that has a significant influence on physical and mental health. Therefore, improving the sense of meaning in life among nursing students has emerged as a crucial concern in nursing education. This study aimed to clarify the profiles and influencing factors of meaning in life among nursing students. Methods A descriptive cross-sectional online survey was conducted among nursing students in China from November 16, 2022, to January 17, 2023. The demographic information questionnaire and the meaning in life questionnaire (MLQ) were used to collect data. Latent profile analysis (LPA) was used to identify groups exhibiting distinct levels of meaning in life. Additionally, univariate analysis and multinominal logistic regression analysis were used to investigate the factors influencing each group. The reporting of this study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist. Results A total of 10,583 valid responses were received, and the analysis revealed four distinct profiles. The profiles identified were the medium meaning group (C1, 41.4%), medium fluctuation meaning-no motivation group (C2, 8.7%), lower meaning group (C3, 9.7%), and higher meaning group (C4, 40.2%). The univariate analysis revealed that age, gender, ethnicity, marital status, educational level, grade, university classification, student leadership experience, and political affiliation were factors that influenced the four latent profiles (P < 0.05). The multinomial logistic regression analysis showed that age, gender, ethnicity, education level, and student leadership experience were significant predictors of the various profiles (P < 0.05). Conclusion There is heterogeneous in meaning in life among nursing students in China. Nursing educators need to provide tailored guidance based on the latent classification characteristics of meaning in life among nursing students, aiming at improving their meaning in life and promoting the development of the nursing workforce.